The monsters we deserve - Sedgwick, Marcus 1968-2022 (Zephyr, an imprint of Head of Zeus Ltd, 2019)
The Villa Diodati, on the shore of Lake Geneva, 1816: the Year without Summer. As Byron, Polidori, and Mr and Mrs Shelley shelter from the unexpected weather, old ghost stories are read and new ghost stories imagined. Born by the twin brains of the Shelleys is Frankenstein, one of the most influential tales of horror of all time. In a remote mountain house, high in the French Alps, an author broods on Shelley's creation. Reality and perception merge, fuelled by poisoned thoughts. Humankind make monsters; but who really creates who? A book about reason, the imagination, and the creative act of reading and writing